Effect of genistein on expression of pancreatic SIRT1, inflammatory cytokines and histological changes in ovariectomized diabetic rat - Yousefi, Hadi (Iran J Basic Med Sci, 2017)
OBJECTIVE(S): Genistein is reported to have anti-diabetic and anti-inflammatory functions, in particular, direct effects on β-cell proliferation and insulin secretion. In this study, we investigated the anti-inflammatory effect of genistein on the pancreatic β-cells in ovariectomized diabetic rat. MATERIALS AND METHODS: Forty female rats were divided into four groups: sham, bilateral ovariectomy (OVX), OVX.D (OVX+diabetes) and OVX.D.G (OVX.D+genistein). After bilateral ovariectomy, rats in the diabetic groups were fed high-fat diet (HFD), ad libitum for 4 weeks, and then a low dose of streptozotocin (STZ) (30 mg/kg) injected intraperitoneally. Genistein (1 mg/kg/day; SC) was administrated for 8 weeks. At the end of 8 weeks, pancreas tissue was removed and used for western blotting and Hematoxylin-Eosin staining. RESULTS: Treatment with genistein declined inflammation and tissue injury, and this decline was correlated with the expression of SIRT1. OVX and OVX.D significantly increased Nf-κB and IL-1β expression and decreased SIRT1 levels compared to sham group (P<0.05). Significant reduction of Nf-κB and IL-1β, and increasing of SIRT1 were observed during genistein treatment (P<0.05). CONCLUSION: Estrogen deficiency alone or with HFD increased pancreatic inflammation. However, subcutaneous administration of gtenistein prevented from these inflammatory changes in the pancreas of a surgery animal model of ovariectomy with or without diabetes. Our results support the potential preventing effect of genistein from pancreatic injury.